Analisis Pengaruh Tingkat Pengangguran Terbuka Terhadap Tingkat Kemiskinan di Provinsi Banten Periode 2018-2022 - Rohmaniah, Inayatur; Wahyuningsih, Dewi; Lutfiah, Adinda; Alidani, Muhamad Sauqi; Desmawan, Deris (Jurnal Informatika, 2024)
The objective of this study is to assess the impact of the open unemployment rate on poverty rates in Banten province from 2018 to 2022. The variables examined include poverty levels as the dependent factor and the open unemployment rate as the independent factor. Employing a quantitative approach, this research utilizes secondary data retrieved from the Central Statistics Agency (BPS) and applies the multiple linear regression analysis technique. The findings indicate that the open unemployment rate variable exhibits a negative and statistically insignificant effect on poverty rates when analyzed individually. This suggests a one-way correlation between open unemployment levels and poverty levels.